Antioxidant and anti-inflammatory properties of water kefir microbiota and its bioactive metabolites for health promoting bio-functional products and applications - Dimitra Papadopoulou; Vasiliki Chrysikopoulou; Aikaterini Rampaouni; Alexandros Tsoupras (AIMS Microbiology)
Inflammation and oxidative stress are implicated in several chronic disorders, while healthy foods and especially fermented beverages and those containing probiotics can provide anti-inflammatory and antioxidant protection against such manifestations and the associated disorders. Water kefir is such a beverage that is rich in both probiotic microbiota and anti-inflammatory bioactives, with an increasing demand as an alternative to a fermented product based on non-dairy matrix with potential health properties. Within this study, the health-promoting properties of the most representative species and strains of microorganisms present in water kefir grains, as well as the health benefits attributed to the bioactive metabolites produced by each individual strain in a series of their cultures, were thoroughly reviewed. Emphasis was given to the antioxidant, antithrombotic, and anti-inflammatory bio-functionalities of both the cultured microorganisms and the bioactive metabolites produced in each case. Moreover, an extensive presentation of the antioxidant and anti-inflammatory health benefits observed from the overall water kefir cultures and classic water kefir beverages obtained were also conducted. Finally, the use of water kefir for the production of several other bio-functional products, including fermented functional foods, supplements, nutraceuticals, nutricosmetics, cosmeceuticals, and cosmetic applications with anti-inflammatory and antioxidant health promoting potential was also thoroughly discussed. Limitations and future perspectives on the use of water kefir, its microorganisms, and their bioactive metabolites are also outlined.